Screening of phosphate accumulating bacteria (pab) from dairy waste water (Funded work) - NEHA SHARMA (International Journal of Pharma and Bio Sciences, 2018)
Phosphorus is recognized as one of the major nutrients required by living organisms involved in sustenance of major physiological processes. In higher concentrations, it can impose toxicological hazards contributing to biomagnification and bioaccumulation in environment. One such example of phosphate accumulation is dairy effluent. Effluents generated by dairy industries are in fluxed with both soluble and insoluble phosphates owing to their origin from different unit processes and operations indigenous to dairy industrial set up. Removal of phosphate from effluents relies upon end-of-pipe treatment strategy encompassing primary, secondary and tertiary stages. The ongoing treatment approach is environmentally benign but is not cost effective and generates enormous volumes of sludge. With an aim to reduce phosphate levels significantly bioremediation was planned which utilised the bio augmentative potential of adapted bacterial isolates from dairy waste water to reduce the level of phosphate to recommended levels. The samples were collected from Jaipur Dairy Effluent Treatment Plant (JDETP) in accordance with standard procedures and screened for phosphate utilising bacterial isolates. The most efficient bacterial strain was biochemically characterised as Escherichia sp. Utilisation of phosphate concomitant with reduction was monitored at regular intervals spectrophotometrically. 63.72% of the phosphate (mgL-1) was found to be removed from synthetic medium after 7 days of incubation whereas 6% abiotic loss of phosphate was also observed under similar physiological conditions. Further studying bacterial diversity of waste water treatment systems could be of fundamental help in obliterating other pollution indicators through bio remedial approach.